Risk factors for cerebrospinal fluid leak in pediatric patients undergoing endoscopic endonasal skull base surgery. (February 2017) - Stapleton, Amanda L.; Tyler-Kabara, Elizabeth C.; Gardner, Paul A.; Snyderman, Carl H.; Wang, Eric W.
Abstract: Objectives: To determine the risk factors associated with cerebrospinal fluid (CSF) leak following endoscopic endonasal surgery (EES) for pediatric skull base lesions. Methods: Retrospective chart review of pediatric patients (ages 1 month to 18 years) treated for skull base lesions with EES from 1999 to 2014. Five pathologies were reviewed: craniopharyngioma, clival chordoma, pituitary adenoma, pituitary carcinoma, and Rathke's cleft cyst. Fisher's exact tests were used to evaluate the different factors to determine which had a statistically higher risk of leading to a post-operative CSF leak. Results: 55 pediatric patients were identified who underwent 70 EES's for tumor resection. Of the 70 surgeries, 47 surgeries had intraoperative CSF leaks that were repaired at the time of surgery. 11 of 47 (23%) surgeries had post-operative CSF leaks that required secondary operative repair. Clival chordomas had the highest CSF leak rate at 36%. There was no statistical difference in leak rate based on the type of reconstruction, although 28% of cases that used a vascularized flap had a post-operative leak, whereas only 9% of those cases not using a vascularized flap had a leak. Post-operative hydrocephalus and perioperative use of a lumbar drain were not significant risk factors. Conclusions: Pediatric patients with an intra-operative CSF leak during EES of the skull base have a high rate of post-operative CSF leaks. Clival chordomas appear to be a particularly high-risk group. The use of vascularized flaps and perioperative lumbar drains did not statistically decrease the rate of post-operative CSF leak.